Analisis Pentingnya Edukasi Lingkungan Anak Usia Dini Melalui Recyle Sampah Sedotan Menjadi Gantungan Kunci Di Madin Al Maksum - Ilun Muallifah; Mamlu’atul Eka Maulida Amaliyah; Zidan Rosyadi Fathan (Universitas Negeri Medan, 2025)
This study aims to analyze the effectiveness of environmental education through a program to recycle waste straws into key chains at Madin Al Maksum. The method used involved training and hands-on practice in utilizing plastic straw waste as an environmentally friendly craft material. The results showed that this activity was able to increase students' awareness and innovation in managing waste in a creative and productive way. This program not only contributed to reducing the amount of plastic waste in the surrounding environment but also awakened an entrepreneurial spirit as an alternative source of income. This study recommends the implementation of a sustainable recycling-based environmental education program to encourage behavioral changes towards better waste management and the importance of protecting the environment